Pengalaman Petani Garam dalam Memanfaatkan Digitalisasi sebagai Strategi Meningkatkan Pendapatan - M. Rofik; Faisol Faisol; Ida Elisa (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
This study aims to explore and understand the experiences of Madurese salt farmers in utilizing digitalization as a strategy to increase income. The method used in this study is a qualitative method with a phenomenological approach, focusing on the subjective experiences of farmers in dealing with and interpreting the use of digital technology. The results of this study indicate that the understanding and utilization of digitalization among Madurese salt farmers is still in its early stages. Some farmers still view digital technology as a social communication tool, while others are beginning to utilize it for marketing, accessing price information, and making economic decisions. The use of WhatsApp and Facebook helps expand markets, improve bargaining power, and open up opportunities for increasing income, although it has not been implemented consistently and in a structured manner. However, the benefits of digitalization have not been felt evenly due to differences in digital literacy, age, experience, and limited internet network infrastructure. These findings are expected to provide a basis for the government and stakeholders to design digital literacy training and online marketing assistance to optimize and equitably utilize technology among farmers.